PELAKSANAAN SANITASI MAKANAN PADA KERETA API DIWILAYAH DAOP VIII TAHUN 2013 - Rizal Oktavianto; A T Diana N; Ema Triastuti (Poltekkes Kemenkes Surabaya, 2014)
Food preparation attempts to serve good quality food through observation to high standard ofhealth and cleanliness, that leads to satisfactory services to the consumers, to be served at reasonableand affordable price and services . Food safety becomes a global issue that needs to be seriouslyconsidered in line with peoples' need and increasingly high demand for food safety.This research was carried out at PT Restorasi KA and aboard the Argo Bromo and Kertajayatrains. Method employed in this research was classified as descriptive analyses with a purpose to describeapplication of food sanitation and hygiene principles for the benefit of the train passengers at a particulartime.Results of observation on food sanitation-hygiene application namely in selection of raw materials67%, food storage 87%, processing of food materials 100%, storage of finished food 90%, transportationof finished food in Argo Bromo 100% and in Kertajaya train 73%, food serving in Argo Bromo andKertajaya 100%, personal hygiene among workers at PT Reska 97%, in Argo Bromo Anggrek train 100%,and in Kertajaya 98%. Tap water used for food processing has satisfied the physical and bacteriologicalrequirements, as well as the bacteriological for finished food and eating utensils.Application food sanitation and hygiene for trains operated in DAOP VIII Area especially in Argo Bromotrain scored a percentage of 95% (meeting the requirements) and in Kertajaya train scored a percentageof 92% (meeting the requirements). Suggestions to PT Reska were concentrated on selection of flour thatrequires some hardness test , and there is a need for more careful sorting of grains, temperatureadjustment in food storage, and to prohibit smoking habit among the workers. Finished and or semifinishedfood storage should be kept off the floor. It is also suggested to provide trolleys in Kertajaya trainfor the transportation of finished food